Historical Background for the Formation of Customer Focus in the Service Sector - V. Konova, Vlada; S. Klyueva, Yuliya; G. Nikolinko, Pouline; A. Bocharov, Vladimir; V. Batsyna, Yana; Yu. Veselova, Anna (International Journal of Psychosocial Rehabilitation, 2020)
Currently, there is the problem of forming the basic provisions for implementing the customer-oriented approach in the management of service entities. The purpose of this paper is to identify patterns and prerequisites for the emergence of a customer-oriented approach in management at different stages of historical development. The methodological basis of the study was formed by theoretical and methodological analysis and synthesis of Russian and foreign scientific literature, conceptual analysis of thematic publications, comparative analysis of different approaches, and methods of induction and deduction in the course of tracing historical and conceptual links with the studied object. The study establishes the link between the periods of development of management science and the emergence of customer-focused theories. The authors substantiate the basic prerequisites for the formation of a customer-focused approach at retail enterprises in Russia. The study resulted in discovering the historical prerequisites for the formation of a client-focused approach in management at different development stages of economics and society as a whole. It took into account external and internal factors concerning the Russian reality. The materials of the paper are of scientific and practical value for understanding the historical background, which allows forming a basis for further study and analysis of the problems of customer focus.